2003
DOI: 10.1590/s0100-29452003000200024
|View full text |Cite
|
Sign up to set email alerts
|

Aclimatização de porta-enxertos de Prunus sp. micropropagados

Abstract: A fase de aclimatização é considerada limitante para a maior parte das plantas micropropagadas pelas altas taxas de perdas que podem acarretar. A cultura in vitro tem determinado, para algumas espécies, a alteração de características morfológicas, anatômicas e fisiológicas que dificultam a sua aclimatização. O objetivo deste trabalho foi avaliar a sobrevivência de plantas dos porta-enxertos de Prunus Capdeboscq e GF677, e das seleções VP411 e VP417 durante o processo de aclimatização. Brotos com 2-3 cm foram i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
1
4
0
5
Order By: Relevance
“…In relation to the percentage of surviving plants (Figure 2c), although not statistically differences were observed, the results were encouraging, probably due to good quality aerial parts and root systems formed during in vitro growth (Figure 2d-g). Similar results have been reported previously for most rootstocks (Vujovic et al, 2012;Zhou et al, 2010), except Gisela 5 (Rogalski et al, 2003a(Rogalski et al, , 2003b.…”
Section: Effect Of Iba Concentration On Acclimatizationsupporting
confidence: 91%
See 1 more Smart Citation
“…In relation to the percentage of surviving plants (Figure 2c), although not statistically differences were observed, the results were encouraging, probably due to good quality aerial parts and root systems formed during in vitro growth (Figure 2d-g). Similar results have been reported previously for most rootstocks (Vujovic et al, 2012;Zhou et al, 2010), except Gisela 5 (Rogalski et al, 2003a(Rogalski et al, , 2003b.…”
Section: Effect Of Iba Concentration On Acclimatizationsupporting
confidence: 91%
“…In our study, poor shoot growth and development was observed in the absence of IBA and at an IBA concentration of 0.3 mg L −1 . According to Rogalski et al (2003b), this phenomenon may be directly related to the effect of IBA on explant apex growth and/or the occurrence of competition between explant apex and root growth. In relation to the percentage of surviving plants (Figure 2c), although not statistically differences were observed, the results were encouraging, probably due to good quality aerial parts and root systems formed during in vitro growth (Figure 2d-g).…”
Section: Effect Of Iba Concentration On Acclimatizationmentioning
confidence: 99%
“…This stage is followed by a process called acclimatization and is essential because the in vitro plants are cultivated under heterotrophic conditions [8]. Morphological anomalies, such as nonfunctional stomata, and physiological anomalies, such as a decrease in photosynthesis, might occur during this process [9]. These anomalies interfere with plant survival in the greenhouse or field.…”
Section: Absence Of Rooting and Acclimatizationmentioning
confidence: 99%
“…These differences were also observed among plants of the same accession in different types of cultures, which may be due to the different requirements these plants have for the tested metabolites. Several studies have demonstrated that during cultivation in vitro, plants undergo alterations in metabolism; for example, gas exchange and photosynthesis decrease (Rogalski et al 2003). These changes could have influenced the accumulation of total and reducing sugar and of amino acids in leaf tissues.…”
Section: Determination Of Amino Acid Total Soluble Sugar and Reducimentioning
confidence: 99%